2018
DOI: 10.1051/matecconf/201824004008
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature on algal biomass growth for biogas production

Abstract: The use of algae is gaining popularity in recent years. Algae can form a suitable substrate for biogas production because they are low in cellulose and have low lignin content. The paper contains a summary with the list of the algae species applied for the biogas production process to this date, coupled with the description of the characteristic conditions in which the process is conducted. The key importance factors during the production of biogas include, among others, grade of algae species used, temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The results showed that temperature (47.2%) and DO concentration (40.2%) were the biggest drivers of biomass growth in the biological treatment process. High temperatures (32.5°C) have shown that they improve the metabolic rate of microorganisms, resulting in high biomass growth [ 35 , 75 , 76 , 77 ]. This indicates that the biological treatment process should be operated at high temperatures (32.5°C) in order to improve the biomass growth.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that temperature (47.2%) and DO concentration (40.2%) were the biggest drivers of biomass growth in the biological treatment process. High temperatures (32.5°C) have shown that they improve the metabolic rate of microorganisms, resulting in high biomass growth [ 35 , 75 , 76 , 77 ]. This indicates that the biological treatment process should be operated at high temperatures (32.5°C) in order to improve the biomass growth.…”
Section: Resultsmentioning
confidence: 99%
“…If too low, it can be limiting for the biomass growth because absorption and scattering phenomena do not let the light penetrate deeply into dense biomass suspension; if present in excess, it can damage vegetative cells and lead to oxidative stress and photoinhibition . Another important factor for the growth of algae is temperature: high values strongly reduce the growth rate and could be fatal for the cells, while low temperatures could significantly decrease biomass productivity . As for nutrients, the most relevant are nitrogen, phosphorus, and carbon, but also micronutrients (e.g., iron, cobalt, and manganese) are required, although in smaller amounts …”
Section: Discussionmentioning
confidence: 99%
“…15 Another important factor for the growth of algae is temperature: high values strongly reduce the growth rate and could be fatal for the cells, 16 while low temperatures could significantly decrease biomass productivity. 17 As for nutrients, the most relevant are nitrogen, phosphorus, and carbon, but also micronutrients (e.g., iron, cobalt, and manganese) are required, although in smaller amounts. 18 In the design used in this work, three are the factors that diversify the various experiments: the light intensity profile, the temperature, and the feeding profile of phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…This range of water temperature can strongly affect the growth rate of algae, the vertical mixture of the freshwater, and the reduction of viscosity [80]. Pawlita-Posmyk et al [81] referred that the warm water temperature between 15°C to 26°C can promote algal growth. The peak nutrient concentrations were observed in this bloom period;…”
Section: Real-time Monitoring For Algal Bloommentioning
confidence: 99%